The Cactaceae family in the Santa Maria river basin (Rio Grande do Sul, Brazil) - de Oliveira, Anabela Silveira; Pontes, Rodrigo Corrêa; Robaina, Luis Eduardo De Souza; Trentin, Romário (Phytotaxa, 2022)
We present a paper dealing, with the family Cactaceae in the Santa Maria River Basin, which were studied by field surveys (2014–2016) and analysis of relevant literature. For each genus, species richness in the study area, general distribution, detailed, maps concerning the study area, and original pictures are provided. The species were assessed according to the IUCN categories and criteria. A key for the identification of the genera in Santa Maria River Basin was proposed. A description of the main found phytophysiognomies (field, saxicola, forest, and wetland), in which the cacti grow, were also given using Walking Method. Twenty-nine Cactaceae taxa were discovered, belonging to the following genera: Parodia (13 taxa, including a nomenclatural change, i.e. P. ritteriana comb. nov. (≡ Notocactus ritterianus), Frailea (7), Gymnocalycium (2), Wigginsia (3), Echinopsis (1), Cereus (1), and Opuntia (1), and Lepismium (1). Five species have a restricted distribution inside area in Santa Maria River Basin. The floristic diversity found in the study area is related to the edaphic and climatic conditions provided by the stony springs in the Santa Maria River Basin, which constitute a favorable microclimate of intense luminosity, heat and humidity for xerophytic species to develop in open areas.